Effect of acetazolamide and subsequent ventriculo-peritoneal shunting on clinical signs and ventricular volumes in dogs with internal hydrocephalus - Kolecka, Malgorzata; Ondreka, Nele; Moritz, Andreas; Kramer, Martin; Schmidt, Martin J.; Justus Liebig University Giessen (My University, 2015)
Background: Acetazolamide is recommended for the reduction of cerebrospinal fluid production in canine internal hydrocephalus. The efficacy of the drug in terms of alleviation of the clinical symptoms and the restoration of normal ventricular volume has not been documented. We hypothesize that acetazolamide inadequately improve clinical signs and has no effect on the ventricular volume. Six dogs with internal hydrocephalus underwent neurological examination and were examined by magnetic resonance imaging, on the day of the diagnosis, after treatment with acetazolamide directly before surgery, and 6 weeks after implantation of a vetriculo-peritoneal shunt due to lack of improvement after medical therapy with 10 mg/kg acetazolamide three times daily (TID). The ventricular volume in relation to the total brain volume was determined on each occasion. The changes in relative ventricular volume and of the neurological status were assessed and compared. Results: McNemar´s test revealed no significant differences in clinical symptoms before and after medical treatment (P > 0.05). However, clinical symptoms changed significantly after surgical treatment (P = 0.001). The ventricle-brain ratio was not significantly changed after therapy with acetazolamide (P > 0.05); however, after subsequent shunt implantation, it was significantly reduced (P = 0.001). Conclusion: Acetazolamide (10 mg/kg TID) showed no effects on clinical signs or ventricular volume in dogs with internal hydrocephalus. After subsequent ventriculo-peritoneal shunting, the dogs had a significantly reduced cerebral ventricular volume and five out of six dogs had no abnormal findings in neurological examination.
Keywords: hydrocephalus; carbonic anhydrase inhibitor; ventriculo-peritoneal shunting; cerebrospinal fluid; ddc:630